Teaching and Learning Through Active Learning in Online Higher Education: Strategies, Challenges, and Future Directions (Beacon: International Journal of Education and Social Studies, 2026)
This study aims to analyze the implementation of active learning in virtual higher education environments using Moodle and to examine lecturers’ perceptions of pedagogical strategies, teaching challenges, and its effectiveness in supporting the learning process. A non-experimental quantitative approach with a descriptive-exploratory design was employed, involving 32 lecturers from the Systems Engineering Department at the University of Córdoba. The research instrument consisted of a Likert-scale questionnaire covering four dimensions: frequency of use, perceived importance, perceived difficulty, and satisfaction level. The results show that lecturers hold positive perceptions of active learning, particularly in enhancing collaboration and communication. However, a gap exists between conceptual understanding and practical implementation, especially in the use of advanced interactive learning strategies. While satisfaction with communication tools is high, challenges remain in developing virtual learning communities and designing interactive learning activities. The study highlights the importance of continuous training and institutional support to enhance the effectiveness of active learning in virtual environments.